Affiliate Stigma and Compassion Satisfaction Amongst Mental Health Service Providers at A Regional Psychiatric Hospital in Nigeria - Joyce, Omoaregba; Blessing, Uteh (Journal of Behavior Therapy And Mental Health, 2019)
Objective Just like their patients, mental health service providers also face stigma. Internalisation of these negative stereotypes could lead to the development of affiliate stigma, reduce their compassion satisfactionand reduce their effectiveness in delivering quality health care to their patients. This study investigated the relationships between affiliate stigma and compassion satisfaction in frontline mental health service providers in a mental health facility in Nigeria. Method This was a cross-sectional study which recruited 183 mental health service providers working in a mental health facility in Nigeria, and who completed questionnaires on affiliate stigma and compassion satisfaction. Results Affiliate stigma among mental health service providers in this study was relatively high (41.5%), and psychiatrists were significantly more likely A to report higher levels of affiliate stigma compared to the psychiatric nurses (p=0.03, OR=0.38,95% CI=0.15 – 0.94). Psychiatrists and Psychiatric nurses who worked for longer hours (> 42 hours per week) reported significantly lower Affiliate stigma (t=2.148, df=28, p=0.04; t=2.118, df=135, p=0.04 respectively). Psychiatrists with high levels of affiliate stigma were more likely to have lower compassion satisfaction, but this was not true of Psychiatric nurses. Mental health service providers who endorse the psychosocial aetiology of mental illness, are significantly more likely to report having experienced high affiliate stigma (F=3.980, df=2, p=0.03). Conclusion The levels of affiliate stigma among mental health service providers in this study was relatively high, particularly among the professional group of psychiatrists. There is an urgent need to address internalization of negative stereotypes among mental health service providers in order to prevent experiences of discrimination among their patients.
Keywords: compassion satisfaction; affiliate stigma; mental health service providers; psychiatric hospital; Nigeria